(untitled) (Boletin Médico de Postgrado, 2024)
Mucormycosis is an infection caused by fungi belonging to the order Mucorales with a low prevalence and high mortality rate which ranges between 40% and 80%. It is associated with immunosuppressed patients, decompensated diabetics or patients with hematological diseases. There are six clinical forms of mucormycosis: rhino-orbito-cerebral, pulmonary, gastrointestinal, cutaneous, renal and disseminated; the first form is the one with the highest progression and morbidity and mortality. We report a case of a 55-year-old female patient who presented a current disease of two months of evolution characterized by bilateral intermittent, self-limited anterior epistaxis, with concomitant fetid greenish anterior rhinorrhea. A CT scan of the nose and paranasal sinuses and endonasal surgical cleaning were performed. The biopsy reported invasive necrotizing rhinosinusitis secondary to mucormycosis infection, so treatment with amphotericin B deoxycholate and posaconazole was started with favorable results.